2011
DOI: 10.1152/physrev.00038.2010
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of the Vasculature for Treatment of Cancer and Other Diseases

Abstract: New vessel formation (angiogenesis) is an essential physiological process for embryologic development, normal growth, and tissue repair. Angiogenesis is tightly regulated at the molecular level. Dysregulation of angiogenesis occurs in various pathologies and is one of the hallmarks of cancer. The imbalance of pro- and anti-angiogenic signaling within tumors creates an abnormal vascular network that is characterized by dilated, tortuous, and hyperpermeable vessels. The physiological consequences of these vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
1,266
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,359 publications
(1,325 citation statements)
references
References 288 publications
(522 reference statements)
47
1,266
2
10
Order By: Relevance
“…Different human cancers are variably sensitive to antiangiogenic drugs (e.g., inhibitors of endothelial TK receptors or antibodies that block vascular growth factors); furthermore, tumors of a generally refractory type may sporadically show dramatic responses to antiangiogenic drugs (Carmeliet and Jain, 2011b; Chung et al., 2010; Goel et al., 2011; Leite de Oliveira et al., 2011). It can be argued that tumor type or subtype‐specific aspects of the biology of associated endothelial cells (e.g., gene expression programs) may have a role in determining such different responses.…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…Different human cancers are variably sensitive to antiangiogenic drugs (e.g., inhibitors of endothelial TK receptors or antibodies that block vascular growth factors); furthermore, tumors of a generally refractory type may sporadically show dramatic responses to antiangiogenic drugs (Carmeliet and Jain, 2011b; Chung et al., 2010; Goel et al., 2011; Leite de Oliveira et al., 2011). It can be argued that tumor type or subtype‐specific aspects of the biology of associated endothelial cells (e.g., gene expression programs) may have a role in determining such different responses.…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…Thus, vascular normalization restores tumor perfusion by fortifying the vessel wall and the vascular network structure, which also decreases interstitial fluid pressure due to the reduced amount of fluid leaking from the vessels. Anti-angiogenic treatments worked well in preclinical models but failed in clinical trials [24], and combinatorial approaches have been employed extensively both in preclinical and clinical studies with varying degrees of success [9,25] whereby the anti-angiogenic drug aims to normalize and not destroy the vessels and it is combined with chemotherapy to eradicate the tumor.…”
Section: Strategies To Improve Drug Deliverymentioning
confidence: 99%
“…Thus, vascular normalization restores tumor perfusion by fortifying the vessel wall and the vascular network structure, which also decreases interstitial fluid pressure due to the reduced amount of fluid leaking from the vessels. Anti-angiogenic treatments worked well in preclinical models but failed in clinical trials [24], and combinatorial approaches have been employed extensively both in preclinical and clinical studies with varying degrees of success [9,25] whereby the anti-angiogenic drug aims to normalize and not destroy the vessels and it is combined with chemotherapy to eradicate the tumor.Apart from anti-angiogenic treatment, tumor perfusion and tumor vessel function can be significantly improved using metronomic chemotherapy [26], in which lower doses of the chemotherapeutic agent are administered more frequently. In fact, metronomic administration is currently being tested in clinical trials, as it was shown to be more efficacious than maximum tolerated dose treatment in preclinical studies [27].…”
mentioning
confidence: 99%
“…It is suggested that even though the leaky and irregular tumor vasculatures seems to provide larger gap to allow the nanoparticles traversing through the tumor interstitial and, eventually, nearby the tumor cells, it also reduces the amount of blood flow resulting in flow stasis and causing high IFP. [154] It is known that most of the tumors have high IFP resulting from irregular vasculatures, which can be a barrier for effective nanoparticle delivery in the tumors. [37] On contrary, to enhance the vascular permeability, vascular normalization strategies aim to transforming the aberrant tumor vasculatures into closely resembling normal vasculatures in order to enhance the structural and functional integrity of the vasculature networks by increasing the pericytes coverage, reducing the IFP and leakiness of the vessels (Figure 5A).…”
Section: Modulating the Tumor Microenvironment For Cancer Therapymentioning
confidence: 99%